2016
DOI: 10.1007/s11099-015-0178-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of methanol on photosynthetic parameters of bean (Phaseolus vulgaris L.) under water deficit

Abstract: Water availability is the main factor limiting crop growth and productivity in dry regions. This study was carried out on bean plants to determine the effect of spraying methanol solution on the photosynthetic characteristics. The main aim of our experiments was to improve plant performance under stress caused by water shortage. Two factors were involved: water deficit stress, such as severe stress (25% of field capacity), mild stress (75% of field capacity), and no stress (100% of field capacity) and applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In this context, the plant's catalase (CAT) activity was investigated, and according to our ndings, a signi cant decrease in the catalase enzyme activity was observed in leaf tissue exposed to 10% and 20% drought stress, compared to the control groups, while it was understood that the enzyme activity continued to decrease with time. Similarly, in a study conducted by Armand (2016) et al on Phaseolus vulgaris, CAT activity in leaf tissues was investigated under drought stress and it was found that there was a decrease compared to control groups. According to the protein analysis, a decrease in stem tissue was seen in the 12th hour when 10% PEG was applied compared to the control groups, and this loss continued to rise with time.…”
Section: Biochemical Responses Of C Sativa To Drought Stressmentioning
confidence: 94%
“…In this context, the plant's catalase (CAT) activity was investigated, and according to our ndings, a signi cant decrease in the catalase enzyme activity was observed in leaf tissue exposed to 10% and 20% drought stress, compared to the control groups, while it was understood that the enzyme activity continued to decrease with time. Similarly, in a study conducted by Armand (2016) et al on Phaseolus vulgaris, CAT activity in leaf tissues was investigated under drought stress and it was found that there was a decrease compared to control groups. According to the protein analysis, a decrease in stem tissue was seen in the 12th hour when 10% PEG was applied compared to the control groups, and this loss continued to rise with time.…”
Section: Biochemical Responses Of C Sativa To Drought Stressmentioning
confidence: 94%
“…Spraying strawberry plants with PPFM resulted in the highest chlorophyll content for the two seasons. Methylobacterium able to improve photosynthetic activity by increasing stomatal count and chlorophyll content in rice plants [27].Spraying methanol has a beneficial impact when combined with Methylobacteria [24]. Florida c.v. plants sprayed with PPFM had the highest interaction chlorophyll values in both seasons followed by Festival c.v. plants with PPFM in the second season.…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…In addition to increasing the yield, some crops showed reduced photorespiration along with an increased cell turgor in plant tissue and an enhanced capacity for photosynthesis during the reproductive stage due to an increase of CO 2 (Nonomura and Benson, 1992). Armand et al (2016) reported that treatment with 20% methanol in beans (Phaseolus vulgaris L.) at the seedling stage resulted in increased net photosynthesis (P N ), intercellular CO 2 concentration (C i ), and a decreased transpiration rate under non-stress conditions.…”
Section: Introductionmentioning
confidence: 99%